Application of Student Worksheets Based on Ethnoscience of Tempe Making on Biotechnology Material to Improve Science Process Skills - Pamudiah, Mutiara Kalyana; Setiawan, Beni (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
The writing of this study aims to describe the improvement of students' science process skills, and the implementation of student worksheets. This research is a Pre-Experimental Design study using the One Group Pretest Posttest Design experiment. The target of this research was students of class IX A and IX B at UPT SMP Negeri 14 Gresik. The results showed that the results of the analysis of the pretest and posttest scores for class IX A experienced an increase in science process skills with an N-Gain of 0.89 with high criteria and in class IX B of 0.83 with high criteria. Based on the results of the implementation of ethnoscience-based student worksheets in class IX A it reached 3.7 in the very good category, while class IX B achieved 3.5 in the very good category.Based on the data obtained, it can be concluded that the application of ethnoscience-based student worksheets can improve the science process skills of UPT SMP Negeri 14 Gresik students